Self-expandable metal stents versus endoscopic balloon dilation for the treatment of strictures in Crohn's disease (ProtDilat study): an open-label, multicentre, randomised trial. (April 2022) - Loras, Carme; Andújar, Xavier; Gornals, Joan B; Sanchiz, Vicente; Brullet, Enric; Sicilia, Beatriz; Martín-Arranz, Maria Dolores; Naranjo, Antonio; Barrio, Jesús; Dueñas, Carmen; Foruny, José Ramón; Busquets, David; et al.
Summary: Background: Endoscopic balloon dilation (EBD) is the established endoscopic treatment for short strictures in Crohn's disease. Fully covered self-expandable metal stents (FCSEMS) have been used for endoscopic treatment of patients for whom EBD was unsuccessful. We aimed to determine the efficacy and safety of the two endoscopic treatments in patients with Crohn's disease with stenosis and compare the mean cost of both treatments. Methods: This multicentre, open-label, randomised trial was done in 19 tertiary and secondary hospitals in Spain. Patients with Crohn's disease with obstructive symptoms and predominantly fibrotic strictures of less than 10 cm in length were eligible for inclusion. We excluded patients with stenosis treated with SEMS or EBD in the previous year and stenosis not accessible to a colonoscope. Patients were randomly assigned (1:1) to receive either EBD (EBD group) or FCSEMS (FCSEMS group) using a digital en-block randomisation system (block size of four). In the EBD group, dilation was done with a CRE Boston Scientific (Marlborough, MA, USA) pneumatic balloon with the diameter set at the discretion of the endoscopist; a maximum of two sessions of dilation were allowed with a minimum interval of 15–30 days between them. In the FCSEMS group, a 20 mm diameter Taewoong (Gimpo-si, South Korea) fully covered metal stent was placed; stent length was set at the discretion of the endoscopist. The primary outcome was to assess the efficacy of the endoscopic treatment, defined by the proportion of patients free of a new therapeutic intervention (EBD, FCSEMS, or surgery) due to symptomatic recurrence at 1 year of follow-up. Patients were analysed according to the intention-to-treat principle. Adverse events were recorded for all the patients; events were considered associated to be with the procedure when a causal association was possible, probable, or definite. This trial is registered with ClinicalTrials.gov, NCT02395354 . Findings: From Aug 28, 2013, to Oct 9, 2017, we assessed the eligibility of 99 patients, of whom 19 (19%) patients were excluded. Thus, 80 (81%) patients were randomly assigned to treatment: 39 (49%) patients to the FCSEMS group and 41 (51%) patients to the EBD group. 33 (80%) of 41 patients in the EBD group and 20 (51%) of 39 patients in the FCSEMS group were free of a new therapeutic intervention at 1 year (odds ratio [OR] 3·9 [95% CI 1·4–10·6]; p=0·0061). Two (3%) of 80 patients had severe adverse events (one [2%] patient in the EBD group and one [3%] patient in the FCSEMS group); both patients had perforations. Interpretation: EBD is more effective than FCSEMS for Crohn's disease strictures, with a good safety profile for both treatments. Funding: Spanish National Institute of Health, Foundation of Spanish Society of Digestive Endoscopy, Catalan Society of Gastroenterology, and Taweoong.